Reactive oxygen species favors Varicellovirus bovinealpha 5 (BoAHV-5) replication in neural cells - Rosales, Juan José (2025)
Varicellovirus bovinealpha (BoAHV) 1 and 5 are closely related neurotropic alphaherpesviruses with distinct neuropathogenic potential. BoAHV-5 causes meningoencephalitis in calves whereas encephalitis by BoAHV-1 infection is sporadic. the mechanisms underlying the differences in tropism and clinical outcomes of the infections are not yet completely understood. Here, we used neuroblastoma SH-SY5Y cells as non-differentiated in comparison with the SH-SY5Y neuronal-like cells obtained after exposing SH-SY5Y undifferentiated cells to trans-retinoic acid. We aimed to establish whether there was a relationship between the production of reactive oxygen species (ROS) and the kinetics of virus replication. We demonstrated that ROS production after BoAHV infection was higher in differentiated cells. Generation of ROS was also dependent on the infecting BoAHV strain. Higher ROS levels were produced during BoAHV-5 infection concomitantly with enhanced viral replication. We propose that increased ROS production mechanistically contributes to the tissue damage and neuroinflammation induced by BoAHV-5 infection. Future studies will determine specific targets of ROS that mediate the effects on viral replication.